Scale-free application layer implementation for ad hoc networks - Gramatikov, Sasho; Filiposka, Sonja; Trajanov, Dimitar; Grnarov, Aksenti (My University, 2007)
The groups of people that use a communication network are a part of some kind of social network. In order to be able to simulate the real life usage of communication networks for human information sharing, in this paper a scale-free application layer, based on social networks properties, is proposed. The simulations show that the social interconnection between the network users has a significant influence on the network performances. The results bring forth a different view on the real life deployment of ad hoc networks when compared to the poor performances of the purely randomized scenarios.
Keywords: ad hoc networks, application layer, scale-free, social networks